2019
DOI: 10.1371/journal.pone.0215860
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic structure and ecological niche modelling reveal signals of isolation and postglacial colonisation in the European stag beetle

Abstract: Lucanus cervus (L.), the stag beetle, is a saproxylic beetle species distributed widely across Europe. Throughout its distribution the species has exhibited pronounced declines and is widely considered threatened. Conservation efforts may be hindered by the lack of population genetic data and understanding of the spatial scale of population connectivity. To address this knowledge gap this research details the first broad scale phylogeographic study of L . cervus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 66 publications
2
29
2
Order By: Relevance
“…All the Stag Beetles were collected by researchers very familiar with the appearance of this species, so confusion with other species of large beetles can be ruled out. Stag Beetles from most of the populations examined here, formed the basis of a recent study on the genetic diversity of this species in Europe, and many of the individual beetles were from an existing collection [8] . In addition, although there are four other members of genus Lucanus in Europe – L. (Pseudolucanus) barbarossa, L. pontbrianti, L. tetraodon and L. ibericus – the materials used for this article were collected outside the geographical ranges of those species.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the Stag Beetles were collected by researchers very familiar with the appearance of this species, so confusion with other species of large beetles can be ruled out. Stag Beetles from most of the populations examined here, formed the basis of a recent study on the genetic diversity of this species in Europe, and many of the individual beetles were from an existing collection [8] . In addition, although there are four other members of genus Lucanus in Europe – L. (Pseudolucanus) barbarossa, L. pontbrianti, L. tetraodon and L. ibericus – the materials used for this article were collected outside the geographical ranges of those species.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…For the analysis we used intact abdomens ( n = 124) with dry internal organs and gut contents, and both elytra ( n = 271); other parts (legs) of the majority of these beetles were also used in the genetic study by Cox et al. [8] . The samples were dried and kept at room temperature until the chemical analysis.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Overijse holds the highest gene diversity and allelic richness of the three populations, though slightly lower levels than those found in surrounding areas of West Europe (Cox et al, 2019).…”
Section: Genetic Bottleneckmentioning
confidence: 66%
“…Population genetic studies of saproxylic insects have typically reported weak genetic structuring over larger geographical ranges than studied here (Komonen & Muller, 2018). Similarly, Cox et al (2019) reported low levels of genetic structure across European stag beetle. This weak genetic structure has often been interpreted as indicating that the species have better than thought dispersal abilities and/or that there exist enough connectivity corridors between populations.…”
Section: Population Genetic Structurementioning
confidence: 71%
See 1 more Smart Citation